Survey on Household Solid Waste Management in Gbado-Lite city (Nord-Ubangi) in the Democratic Republic of the Congo - Koto-te-Nyiwa Ngbolua; Ruphin Djolu Djoza; Gina Wediani Ngbaisi; Colette Masengo Ashande; Clarisse Falanga Mawi; Monizi Mawunu; Clément Inkoto Liyongo; Jeff Iteku Bekomo (Britain International for Academic Research (BIAR) Publisher, 2022)
Household solid waste management is a crucial issue for environmental and human health. The purpose of this study was to conduct a survey on household solid waste management in Gbado-Lite (Nord-Ubangi) in the Democratic Republic of Congo (DRC). A household solid waste survey was conducted in 5 neighborhoods of the city of Gbado-Lite in northern DRC from July to August. Data collection was made possible by stratified probability sampling and direct observations. The results of this study revealed that the main informants (75%) were women and 68% of the respondents were in the 18-35 age group. The main socio-cultural groups in the study area are the Ngbadi (55%) and Ngbaka (16%). In addition, 74% of respondents have secondary education and their main sources of income are commerce (25%), the civil service (20%) and the household (13%). Also, the main solid household wastes identified were organic materials (44%) and packaging (25%); the majority (56%) of respondents did not have garbage cans and used plastic buckets without lids as their main garbage can (75%). Almost all (98%) of the waste does not undergo primary separation. The main waste disposal methods used by households are: landfill (43.87%), abandonment on public land (30.62%) and incineration (18.36%). Finally, the main harms of waste reported are: typhoid fever (29%), malaria (25%) and mosquito proliferation (24%). It is therefore desirable that a public sanitation service be set up in Gbado-Lite to enable households to manage their solid waste properly and thus protect the urban environment and human health.